Evaluation of intravarietal polymorphism of tomato fungal disease resistance genes in Michurinsky State Agrarian University breeding varieties - I. N. Shamshin; A. S. Ilyichev; E. V. Grosheva (Овощи России, 2022)
Relevance. The studies are aimed at assessing the intravarietal allelic diversity of genes for resistance to fusariosis and cladosporiosis of tomato cultivars bred at the Michurinsky State Agrarian University using molecular markers.Methods. The biological objects of the study are tomato varieties bred at the Michurinsky State Agrarian University. A total of 10 varieties were analyzed. The assessment of intravarietal polymorphism was determined on a sample of 10 plants of each variety. DNA extraction was performed using a Quick-DNA Plant/Seed Miniprep Kit (Zymo Research, USA) for DNA extraction according to the manufacturer's protocol. The P7 DNA marker was used to identify the cladosporosis resistance gene Cf-19. The presence of the fusarium wilt resistance gene I-2 was determined using the marker I-2/5. Amplification results were visualized by electrophoresis in 2% agarose gel.Results. 10 plants of 10 varieties of Michurinsky GAU selection tomato were analyzed using molecular markers of genes for resistance to cladosporiosis and fusariosis. An assessment of intravarietal polymorphism was carried out. In most of the varieties studied, the genes analyzed are identified in a heterozygous state. Three varieties (Vivat, Carotinka, Krasavets) containing only alleles of susceptibility to the causative agent of the disease in the genotype I-2 identified by the gene. Individual samples were homozygous for the fusariosis resistance allele. Analysis of the gene for Cf-19 resistance to cladosporiosis showed that most of the varieties studied are heterozygous forms. In some varieties, all ten plants were heterozygous. These include Krasavets, Vivat, Orlik, Bui Tour. The remaining samples had different allelic compositions. The pathogen resistance allele has been identified in plants of the Nepryadva and Chernysh varieties. The dominant allele in the homozygous state was detected in the Japanese variety. At the same time, all the analyzed plants of this variety were monotonous.Conclusion. It has been established, but a significant part of the varieties of tomato selection of Michurinsky GAU is polymorphic in the genes for resistance to cladosporiosis and fusariosis. In this case, a significant part of the varieties can be used in selection during preliminary molecular analysis. According to the gene for resistance to fusariosis, the following varieties are identified sources of the resistance allele: Sokol, Nepryadva, Yaponchik, Orlik, Zolotnichok, Chernysh. In them, the gene is I-2 represented in a heterozygous state. Intraortic polymorphism was also noted for the Cf-19 gene. Most samples have two alleles. The exception is the Japanese variety, which is the dominant homozygote for this gene.